ASSESSING THE SUITABILITY OF GROUNDWATER FOR DRINKING AND AGRICULTURAL USES IN THE ZACHARO BASIN, SW PELOPONNESUS - Panagopoulos, G.; Lambrakis, N.; Chalvantzis, C.; Bekiari, V.; Avramidis, P. (Bulletin of the Geological Society of Greece, 2016)
The hydrochemical character of the Zacharo basin groundwaters and their suitability for drinking and irrigation purposes are evaluated in this paper. The Pindos karst aquifer, the Neogene and the alluvial aquifer are the three most mportant aquifers of the study area. 46 water samples were taken from wells, boreholes and spring and they analyzed for the physicochemical parameters (pH, EC and TOC), major ions (Ca2+, Mg2+, Na+, K+, NH4+, HCO3-, Cl-, F-, SO4 2- and NO3-) and trace metals (B, Fe, Mn, Cr, Pb, Se, Ni). The suitability of groundwaters for drinking and irrigation is evaluated by the calculation of Water Quality Index and the indices SAR, %Na, RSC and KR. The water of the karstic and alluvial aquifer is of “excellent” quality for both uses. On the other hand, the Neogene aquifer shows serious problems in respect with the degradation of water quality, since 20% of the samples are of “poor” and “extremely poor” quality for drinking purposes and 33% are “unsuitable” for irrigation. The degradation of water quality is attributed to natural processes of enhanced ion exchange, since the cation exchange capacity of the aquifer materials is increased due to the presence of clay minerals and organic matter.